Conversão de resíduo agroindustrial na produção de bioemulsificante por stenotrophomonas maltophilia UCP 1601 e aplicação na remoção de poluente hidrofóbico. - Nogueira, Ianne Batista (2019)
Biosurfactants are active surface molecules produced by microorganisms that have received increasing interest considering the advantages they have over chemical surfactants, such as biodegradability, low toxicity, production from renewable sources, and functionality under extreme conditions of pH, temperature and stability. The studies were carried out evaluating the potential of biosurfactant and emulsifier by the bacterium Stenotrophomonas maltophilia UCP 1601, isolated from clay soil on the banks of the Capibaribe River (PE, Brazil), with sensitivity to the antibiotics ceftazidine, levofloxacin, minocycline, chlorofenicol, norfloxacin, erythromycin and nitrofurantoin; and demonstrated resistance to clindamycin, cefdoxacin and amoxicillin. In this sense, the hemolysis test was used in sheep blood agar to evaluate the production of biosurfactant by S. maltophilia, with halo of 9 mm. After the confirmation of the biosurfactant production, investigations were carried out with submerged fermentation in saline mineral medium supplemented with 10% post-fry soybean oil (PFSO), different concentrations of glucose, peptone, ZnCl2 and MgSO4, according to a % glucose, 1% Peptone, 2.72% ZnCl2 and 2.46% MgSO4) had a high emulsification rate of 82.74% with burned engine oil. Other studies were carried out with the bioemulsifier to evaluate stability, characterization and environmental application. The bioemulsifier was stable under the tested conditions of different temperatures, pH and sodium chloride concentrations and confirmed by the emulsification index (IE24) of 78.57, 54.07 and 58.62%, using soybean, corn and diesel, respectively. The yield of the bioemulsifier produced by the submerged fermentation was 2.8 g / l, presenting an anionic character, with a molecule constituted by proteins (28.2%), carbohydrates (14.7%) and lipids (37.6%), indicating a polymeric biomolecule. The new bioemulsifier demonstrated promising potential for areas contaminated with hydrophobic compounds, exhibiting the ability to reduce the viscosity of residual soybean oil and burned engine oil, as well as excellent dispersion capacity of burnt-out engine oil with an area of 69.94 cm2 oil displacement (ODA), in addition to removing 71.7% of the oil derivative from the sandy soil. The results obtained with the bioemulsifier produced by S. maltophilia indicate its applicability in promising processes of bioremediation of areas contaminated with hydrophobic compounds.